2017
DOI: 10.1007/s11060-017-2725-0
|View full text |Cite
|
Sign up to set email alerts
|

Update on the effect of exogenous hormone use on glioma risk in women: a meta-analysis of case-control and cohort studies

Abstract: Various studies have confirmed the important roles of endogenous hormones in the development of gliomas, while the roles of exogenous hormones remain controversial. Based on case-control studies and cohort studies, a meta-analysis was exerted to explore the effect of two exogenous hormones use (HRT: hormone replacement therapy; OC: oral contraceptives) on glioma risk. 16 eligible studies, including 11 case-control studies and 5 cohort studies, containing 8055027 women, were included in our study. All included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Several teams showed that the risk of developing GBM is reduced in women who have taken contraceptives or hormone replacement therapy (HRT) containing a mixture of estrogens and progestins suggesting a protective role of the female hormone, whereas other studies reported a deleterious effect of pregnancy on glioma anaplastic progression [50][51][52].…”
Section: Clinical Data: the Female Hormone Paradoxmentioning
confidence: 99%
See 1 more Smart Citation
“…Several teams showed that the risk of developing GBM is reduced in women who have taken contraceptives or hormone replacement therapy (HRT) containing a mixture of estrogens and progestins suggesting a protective role of the female hormone, whereas other studies reported a deleterious effect of pregnancy on glioma anaplastic progression [50][51][52].…”
Section: Clinical Data: the Female Hormone Paradoxmentioning
confidence: 99%
“…In order to explain the differential incidence between men and women, many studies addressed the impact of exogenous hormone intake on glioma onset. A recent meta-analysis carried out on five patient cohorts and 11 case-control studies for a total of 8,055,027 women addressed the effect of exogenous hormone use on glioma risk [52]. The age of the patients was very variable among the selected studies preventing an age-related analysis.…”
Section: Contraceptive Pills and Hormone Replacement Therapy: The Twomentioning
confidence: 99%
“…[ 14 ] In congruence, recent meta-analysis studies show that women who have used exogenous estrogen (either oral contraceptives or hormone replacement therapy) have lower risk of glioma compared to nonusers. [ 15 16 ] It is known that steroid hormones can easily pass through the blood–brain barrier. [ 17 ] Moreover, enzymes responsible for the synthesis of estrogens and androgens have also been detected in GBM cells, along with the expression of their respective receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, in 2018, a meta-analysis of casecontrol and cohort studies showed that a decreased risk of gliomas is associated with the use of hormonal contraceptives and hormone replacement therapy. Despite the contradictions, the evidence suggests that the use of exogenous female gonadal steroid hormones decreases the probability of developing a glioma [97], which supports the idea of female gonadal steroid hormones' protection against glioma development. However, it is essential to note that the most used contraceptives combine estrogens and progestins, then the effects of this therapy are caused by this combination, and not by only estrogens or only progestins.…”
Section: Risk Of Glioblastoma Associated To Exogenous Female Gonadal Steroid Hormonesmentioning
confidence: 60%